From Wargames to Wfh. (19th June 2021) - O'Connor, Patrick
Abstract: Patrick O'Connor MBCS, Principal Systems Analyst Programmer at Amadeus, writes about the evolution of the PC: from the excitement of the first IBM PC‐XT clone, to VPNs.